PENDEKATAN KONSEPTUAL DALAM PROSES PERANCANGAN INTERIOR - Santosa, Adi (Institute of Research and Community Outreach - Petra Christian University, 2005)
The goal of the process of interior designing is to solve the complex problems related to the respond of human towards space. An appropriate design concept is needed to solve the problems integrally. The success of the design concept depends on the approach of development process. The conceptual approach can be developed by first understanding some points%2C such as: the component of design knowledge%2C the scheme of analytical designing%2C the mapping of the way of thinking of design%2C the methodology of design approach%2C that are all then finalized by the formulation of the design concept. By understanding those points%2C a complex design problem can be simplified into a clear and systematic classification and hence%2C an exact design concept can be processed easily. Finally%2C the precise design concept will be capable of integrating the result of design into a complete unimpaired one. Abstract in Bahasa Indonesia : Proses perancangan interior bertujuan untuk memecahkan masalah yang kompleks berkaitan dengan respon manusia terhadap ruang. Untuk dapat memecahkan masalah secara utuh maka diperlukan sebuah konsep perancangan yang tepat. Keberhasilan konsep perancangan tergantung pada pendekatan yang dilakukan dalam proses penyusunannya. Pendekatan konseptual dapat dibangun dengan cara memahami beberapa hal%2C meliputi: komponen pemahaman desain%2C skema perancangan analitis%2C pemetaan pola pikir desain%2C metode pendekatan desain%2C dan diakhiri dengan perumusan konsep desain. Dengan memahami hal-hal tersebut maka sebuah permasalahan desain yang kompleks dapat disederhanakan ke dalam klasifikasi yang jelas dan sistematis%2C sehingga proses penyusunan konsep perancangan yang tepat dapat dilakukan dengan lebih mudah. Konsep yang tepat pada akhirnya akan mampu mengikat hasil perancangan menjadi sebuah desain yang terintegrasi secara utuh. approach%2C conceptual%2C designing%2C interior.